The Ability of Students’ in Distinguishing between Facts and Opinions in Reading English at SMA Negeri 2 Kota Jambi - Rice Indri Nilawati; Suyadi Suyadi (Universitas Batanghari Jambi, 2020)
This research is a descriptive study using quantitative descriptive method. This study aims to describe the ability of students to distinguish facts and opinions in reading English texts at SMAN 2 Kota Jambi. The object of this study amounted to 27 students’ of SMA Negeri 2 Kota Jambi. The researcher used random sampling technique in determining the object of the research. In collecting data, researcher used open ended questionnaire. The number of tests given is 10 questions in each text. Data in this study were obtained from the results of tests given to students’. The results of this study based on the results of the analysis of 27 students’ were 9 students get a score of 80-100 which is categorized as & quot; Excellent & quot; (A) with sample code of students 1, students 2, students 4, students 5, students 7, students 8, students 13, students 23, 7 students get a score of 66-79 categorized & quot; Good & quot; (B) with sample code of students 3, students 10, students 17, students 18, students 19, students 21, and students 24, 7 students score 56-65 categorized as & quot; Fair & quot; (C) with sample code of students 6, students 9, students 15, students 22, students 25, students 26 and students 27, 4 students get a score of 40-55 categorized as & quot; Poor & quot; (D) with a sample code of 11 students, 12 students, 16 students, and 20 students. So, students' ability to distinguish between facts and opinions in reading English texts in class XI students of SMA Negeri 2 Kota Jambi is categorized at the level & level based on per- forance; Excellent & qout (A) contains the average scores of students’.Key words: Students’ Ability, Facts and Opinions, Reading English.